Implementing and Communicating Optimal Monetary Policy - Amund Holmsen; Jan F. Qvigstad; Øistein Røisland (Norges Bank, 2007)
The interest rate forecast plays a key role in the communication of monetary policy in Norges Bank. We give a comprehensive overview of the Bank's communication with focus on the interest rate forecast. The main arguments for publishing the interest rate forecast are discussed. The arguments are validated against two years of experience with interest rate forecasting. The paper describes the implementation of monetary policy in the Bank's models, in particular the use of optimal policy under commitment. It is argued that using optimal policy in a 'timeless perspective' is a useful normative benchmark to support a consistent reaction pattern that utilises the expectations channel appropriately. Comparing the interest rate forecasts with the market forward interest rates indicates that the bank's reaction pattern has been reasonably well anchored in the financial markets.
hdl:11250/2507972
Keywords: 330